Procalcitonin-guided antibiotic therapy in elderly ICU patients with severe pneumonia: a retrospective analysis of biomarker dynamics - Liu, Xuehui; Chen, Renzhi; Wen, Li (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to explore the significance of procalcitonin (PCT) dynamics in guiding antibiotic therapy for severe pneumonia in elderly intensive care unit (ICU) patients.MethodsWe retrospectively analyzed 355 elderly patients with severe pneumonia admitted to our ICU between January 2022 and December 2024. Patients were divided into a PCT-guided group (n = 195) receiving biomarker-directed therapy and a control group (n = 160) receiving conventional empirical treatment. We measured serum PCT, white blood cell count (WBC), high-sensitivity C-reactive protein (hs-CRP), and other inflammatory markers at specific time points. Key outcomes included antibiotic usage parameters, APACHE II scores, and time to normalization of laboratory values.ResultsThe two groups showed comparable baseline characteristics (p > 0.05). After treatment, both groups exhibited significant improvement in inflammatory markers, with the PCT-guided group demonstrating more pronounced reductions (p < 0.05). The PCT-guided group showed superior antibiotic stewardship outcomes, including reduced antibiotic usage duration, fewer antibiotic agents used, lower antibiotic utilization intensity, and shorter ICU stay (all p < 0.05). Additionally, this group achieved faster normalization of laboratory parameters (p < 0.05) and lower post-treatment APACHE II scores (p < 0.05).ConclusionThis study indicates that PCT-guided antibiotic therapy may optimize treatment strategies, potentially improve clinical outcomes, and enhance antibiotic stewardship in elderly ICU patients with severe pneumonia. Further studies are needed to establish optimal PCT cutoff values and evaluate its combined use with other biomarkers.